Coaching Clinic Peningkatan Profesional Guru melalui Karya Ilmiah bagi Guru Sekolah Dasar - Syunu Trihantoyo; Shelly Andari; Mohamad Syahidul Haq (PUCUK REBUNG: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The era of the Education Revolution 4.0 has now been felt and become a part of the education process and has an impact on the action of realizing teacher professionalism. With regard to educational issues as stated above, the purpose of implementing this article is to provide knowledge and skills for teachers in making classroom action research reports so that they can increase their professionalism. The method of this training activity is carried out by lectures, discussions, questions and answers, and mentoring. This activity was attended by 24 participants from elementary school teachers throughout the city of Surabaya who had filled out the online registration (google form). The result of this training was that the knowledge and skills of teachers increased and were able to lead to the realization of professional teachers. This can be seen from the results of the training evaluation data analysis, which overall participants rated this activity in the very satisfactory category with a score range of 55-64. The training materials that have been mastered by the participants are good practice in classroom learning, the nature of classroom action research reports, writing classroom action research reports, and disseminating classroom action research reports. Mentoring is done by reviewing class action research reports from participants to be presented and provide feedback for improvements. Dissemination by submitting relevant educational journals and classroom action research journals to be published from the trainees.